2020
DOI: 10.1093/ajcn/nqaa254
|View full text |Cite
|
Sign up to set email alerts
|

Exploring changes in the human gut microbiota and microbial-derived metabolites in response to diets enriched in simple, refined, or unrefined carbohydrate-containing foods: a post hoc analysis of a randomized clinical trial

Abstract: Background Dietary carbohydrate type may influence cardiometabolic risk through alterations in the gut microbiome and microbial-derived metabolites, but evidence is limited. Objectives We explored the relative effects of an isocaloric exchange of dietary simple, refined, and unrefined carbohydrate on gut microbiota composition/function, and selected microbial metabolite concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Previously reported evidence supports our findings. Evidence from a randomized diet intervention trial aiming to examine the effect of carbohydrate type on gut microbial composition and function and metabolites showed that Anaerostipes had a higher abundance after a simple carbohydrate diet compared to a refined carbohydrate diet [33]. Due to the role of Anaerostipes as a butyrate producer, low abundance after the consumption of refined carbohydrate foods may contribute to the unfavorable effects of diets rich in refined carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported evidence supports our findings. Evidence from a randomized diet intervention trial aiming to examine the effect of carbohydrate type on gut microbial composition and function and metabolites showed that Anaerostipes had a higher abundance after a simple carbohydrate diet compared to a refined carbohydrate diet [33]. Due to the role of Anaerostipes as a butyrate producer, low abundance after the consumption of refined carbohydrate foods may contribute to the unfavorable effects of diets rich in refined carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other metabolites (including lipopolysaccharide, branched-chain amino acid and bile acids) from the gut microbiota may also play an important role in insulin resistance [ 55 ]. For example, Faits et al found that consuming an unrefined carbohydrate diet resulted in a significant increase in abundance of Roseburia , as well as a decreased concentration of secondary bile acid [ 56 ]. Results from another randomized controlled crossover feeding study suggested that whole grain consumption led to significant increases in circulating concentrations of taurolithocholic acid, taurocholic acid, and glycocholic acid; moreover, significant associations between bile acids and HOMA-IR were also found in this study [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roseburia abundance was higher and the secondary bile acids lithocholic acid and deoxycholic acid were lower after consumption of the unrefined carbohydrate diet relative to the simple carbohydrate diet. There were no changes in SCFA with either diet (Faits et al., 2020). The most recent study investigated the intake of whole‐grain wheat versus refined wheat in adults with overweight or obesity (van Trijp et al., 2020).…”
Section: Effects Of Whole Grain On Microbiota Composition and Activitymentioning
confidence: 99%
“…In a randomized cross‐over study, Faits et al. (2020) fed 11 subjects three diets for a period of 4.5 weeks with a 2‐week washout between diets. The diets were labeled either simple, refined, and unrefined carbohydrate diets, differing in the dominant type of carbohydrate.…”
Section: Effects Of Whole Grain On Microbiota Composition and Activitymentioning
confidence: 99%